Frequency of Proteinuria in Newly Diagnosed Diabetic Patients Presenting to the Medicine Ward of District Head Quarter Hospital, Dera Ismail Khan - Umama, Narmeen; Masood, Ihsan Ullah; Khan, Abdurrhman (Biological and Clinical Sciences Research Journal, 2025)
Diabetic nephropathy can develop early in the course of diabetes mellitus, often presenting initially as proteinuria and contributing significantly to long-term morbidity. Objective: To determine the frequency of proteinuria in newly diagnosed diabetic patients presenting to the medicine ward of the district headquarters hospital, Dera Ismail Khan. Methodology: The present study was conducted on 210 patients aged 30 to 75 years who were newly diagnosed with diabetes mellitus; diabetes was confirmed on two separate fasting plasma glucose tests with fasting glucose >126 mg/dL. Patients were assessed for proteinuria, which was defined as protein excretion greater than 150 mg/day. SPSS 26 was used for analysis. Associations were evaluated using the Chi-square test, with p-values < 0.05 considered significant. Results: The Mean age of the cohort in the present study was 52.46±13.51 years. The majority of the cohort was male (58.1%). Hypertension was observed in 42.9% cases. Proteinuria was diagnosed in 92 (43.8%) cases. Proteinuria was significantly associated with older age (p = 0.008) and hypertension (p = 0.0001). Conclusion: A high frequency of proteinuria (43.8%) was found among newly diagnosed diabetic patients presenting to the medicine ward. Older age and hypertension were significantly associated with proteinuria in the present study.